2011
DOI: 10.1111/j.1474-9726.2011.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cellular senescence mechanisms in human corneal endothelial cells

Abstract: The human cornea is a tri-laminar structure composed of several cell types with substantial mitotic potential. Age-related changes in the cornea are associated with declining visual acuity and the onset of overt age-related corneal diseases. Corneal transplantation is commonly used to restore vision in patients with damaged or diseased corneas. However, the supply of donor tissue is limited, and thus there is considerable interest in the development of tissue-engineered alternatives. A major obstacle to these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
6
22
0
Order By: Relevance
“…The majority of primary cells from the 21M donor senesced at passage 9 and was not responsive to hTERT immortalization (Figure 1I), consistent with a recent report indicating that hTERT expression alone does not overcome senescence-related growth arrest in primary HCEnCs [39]. However, the subpopulation of primary cells designated HCEnC-21 did not show any signs of cellular senescence for more than 70 passages and was conducive to retrovirally mediated hTERT immortalization.…”
Section: Discussionsupporting
confidence: 88%
“…The majority of primary cells from the 21M donor senesced at passage 9 and was not responsive to hTERT immortalization (Figure 1I), consistent with a recent report indicating that hTERT expression alone does not overcome senescence-related growth arrest in primary HCEnCs [39]. However, the subpopulation of primary cells designated HCEnC-21 did not show any signs of cellular senescence for more than 70 passages and was conducive to retrovirally mediated hTERT immortalization.…”
Section: Discussionsupporting
confidence: 88%
“…The relationship with male gender is likely to be related to the anti-oxidant and anti-inflammatory properties of oestrogen [20], while the relationship with low current CD4 count suggests that poor immune restoration may accelerate senescence. Our finding that UV exposure and smoking were also independent predictors of polymegathism in the overall study population and in HIV-infected individuals supports the findings of others that stress, including oxidative stress, is likely to be an important contributor to cellular senescence mechanisms in HCECs [30]. Our observation of increased CDKN2A levels in PBLs from HIV-infected individuals compared with HIV-seronegative individuals supports the mechanism of systemic oxidative stress.…”
Section: Discussionsupporting
confidence: 88%
“…[22] P21 plays a role in senescence of CECs: it was found to be transcriptionally increased in CECs undergoing replicative senescence, and at the protein level in CECs cultured from old donors. [23, 24] The results of the present study demonstrate in a large number of specimens that enhanced nuclear p21 expression can be found in the endothelium of FECD corneas. A study by Azizi et al recently demonstrated that p53-protein is increased in the endothelium of FECD corneas.…”
Section: Discussionsupporting
confidence: 60%
“…[27] It was previously shown that p16 mRNA is increased in both cultured human CECs at high passages and donor corneas from old donors and that it was elevated at the protein level in cultured CECs from old donors. [23, 24, 28] In our study, intense p16-reactivity in individual scattered CECs among p16-negative CECs was a common finding on the stained FECD TMA core-sections (Figure 3). This stood in strong contrast to the uniform, generally weak endothelial p16 expression in most of the control corneas (Figure 3).…”
Section: Discussionsupporting
confidence: 57%